2007
DOI: 10.1158/1055-9965.epi-07-0378
|View full text |Cite
|
Sign up to set email alerts
|

Meat and Meat-Mutagen Intake and Pancreatic Cancer Risk in the NIH-AARP Cohort

Abstract: Meat intake, particularly red meat, has been positively associated with pancreatic cancer in some epidemiologic studies. Detailed meat-cooking methods and related mutagens formed in meat cooked at high temperatures have not been evaluated prospectively as risk factors for this malignancy. We investigated the association between meat, meat-cooking methods, meat-mutagen intake, and exocrine pancreatic cancer in the NIH-American Association of Retired Persons (NIH-AARP) Diet and Health Study cohort of 537,302 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 48 publications
(88 reference statements)
5
129
3
1
Order By: Relevance
“…11,13 In addition, some other studies have observed positive associations with meat-derived HCAs and benzo(a)pyrene, a marker of PAHs, and pancreatic cancer risk. 11,41,42 Regarding fresh red meat intake, we observed a statistically significant inverse association with pancreatic cancer among microscopically verified cases, although this decrease was only observed for the highest versus the lowest quintile. The risk estimates for red meat intake seemed to change, however, during follow-up, although the interaction with time was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,13 In addition, some other studies have observed positive associations with meat-derived HCAs and benzo(a)pyrene, a marker of PAHs, and pancreatic cancer risk. 11,41,42 Regarding fresh red meat intake, we observed a statistically significant inverse association with pancreatic cancer among microscopically verified cases, although this decrease was only observed for the highest versus the lowest quintile. The risk estimates for red meat intake seemed to change, however, during follow-up, although the interaction with time was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…3 To date, 11 cohort studies have investigated the relation between the intake of total meat, different meat types and eggs and pancreatic cancer risk. 3,6,[8][9][10][11][12] Two studies have observed a positive association with total meat intake, 3,11 the Multiethnic Cohort Study has observed increased risks with the intake of beef and pork, 3 and a cohort among 7th-day Adventists has observed a positive association with egg intake. 3 Inverse associations were observed with the intake of pork in a study of Swedish twins 8 and with the intake of poultry among Swedish women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been associated to the fact that smoked food contains Heterocyclic Amines (HCAs) and Polycyclic Aromatic Hydrocarbons (PAHs) chemicals formed when muscle meat, including beef, pork, fish, and poultry, is cooked using high-temperature methods, such as pan frying or grilling directly over an open flame is said to predispose to cancer generally [21]. Previous studies have reported that high consumption of well-done, fried, or barbecued meats was associated with increased risks of colorectal [22], pancreatic [23,24], and prostate [24,25] cancer. There is therefore a probability of association in our population cohort in relation to prostate cancer.…”
Section: Discussionmentioning
confidence: 99%